The Evocation Situated in Latin America as the Identitarian Basis in Los pasos perdidos (Letras, 2025)
In Los pasos perdidos (1953) by Alejo Carpentier, memory does not emerge in isolation, but rather as an experience connected to the territory. This article proposes a reading centered around the way in which the protagonist’s memory, through remembrances both deliberate and involuntary, is engaged by contact with space, and how this process allows rebuilding the link between past, desire, and identity. This study approaches the context in which every remembrance occurs and recognizes the decisive role of Latin America’s territory as their trigger. From this perspective, it proposes a reading of this work, one which places memory as a central axis of the narrative, and key to understanding the process of identity for the character.
Keywords: Memory; Spatiality; Identity; Latin America; Remembrances; Sensorial